Efficient metal ink ultrasonic-assisted sintering method
Through the ultrasonic assisted sintering method, the problems of unsatisfactory conductivity and substrate damage at high temperatures are solved, high-quality sintering at low temperatures are achieved, and the conductivity and applicability are improved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411641071.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-07
AI Technical Summary
The existing metal ink sintering methods cause poor conductivity, substrate damage and high energy consumption at high temperatures, making it difficult to meet the requirements of conductivity, low temperature processes and substrate compatibility at the same time.
Ultrasonic assisted sintering method is adopted to significantly reduce the sintering temperature, improve the conductivity, and expand the types of substrates that can be used through low-temperature presintering and local frictional heat generation and plastic deformation caused by ultrasonic waves.
It significantly improves the conductive properties of the conductive patterns, reduces substrate damage, and reduces energy consumption, making it suitable for large-scale industrial applications.
Smart Images

Figure CN119277662A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of additive manufacturing, and in particular to a high-efficiency metal ink ultrasonic-assisted sintering method. Background Art
[0002] At present, the conventional metal ink sintering method usually includes two steps: first, the ink is pre-sintered by heating the printed substrate to volatilize most of the solvent in the ink, and then the formal sintering is performed using near-infrared or flash lamps; this method requires the substrate to maintain a high temperature to ensure the bonding quality between the metal particles and the final conductivity. However, high temperature treatment will lead to the following problems:
[0003] 1. The porosity of the conductive pattern after sintering is high and the conductive performance is not ideal.
[0004] 2. High temperature has a serious damaging effect on printing substrates and dielectric materials, limiting the choice of materials and substrates, especially for flexible substrates.
[0005] 3. High temperature also increases energy consumption and production costs, which is not conducive to industrial-scale application.
[0006] Therefore, how to achieve high-quality metal ink sintering at a lower temperature, improve conductivity and reduce damage to the substrate has become a difficult problem in current research. Existing technologies are difficult to simultaneously meet the requirements of conductivity, low-temperature process and substrate compatibility, and a new technical solution is urgently needed to solve these problems. Summary of the invention
[0007] In order to solve the technical problems in the above-mentioned prior art, the purpose of the present invention is to propose an efficient metal ink ultrasonic assisted sintering method. By introducing ultrasonic waves, the temperature requirement in the sintering process can be significantly reduced, so that the substrate material is not easily damaged by heat, thereby expanding the types of substrates that can be used, such as flexible plastics, paper substrates, etc.; at the same time, through the local friction heat generation and plastic deformation induced by ultrasonic waves, the metal particles can be more tightly combined, which can significantly reduce the sintering temperature and improve the conductive performance of the conductive pattern; the present invention has the advantages of simple process, little damage to the substrate, and excellent conductive performance.
[0008] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:
[0009] A high-efficiency ultrasonic-assisted sintering method for metal ink comprises the following steps:
[0010] Step 1: Apply metal ink to the surface of the substrate to form a conductive pattern with a preset thickness;
[0011] Step 2: After the metal ink is coated, the substrate with the conductive pattern in step 1 is pre-sintered at a low temperature to evaporate part of the solvent in the metal ink;
[0012] Step 3: Apply ultrasonic waves to the surface of the conductive pattern pre-sintered in step 2 to continue low-temperature sintering at a constant temperature, and finally form a dense conductive pattern.
[0013] In step 1, the metal ink is nano silver ink or nano copper ink, the metal ink has a viscosity of 1-10 mPa·s, and a surface tension of 25-45 mN / m.
[0014] The metal ink is prepared from a solute, an organic solvent and a dispersant. The solute is nanosilver or nanocopper particles with a particle size of 20-100 nm, the organic solvent is propanol, ethanol or ethylene glycol, and the dispersant is polyvinyl pyrrolidone (PVP); the mass percentages of the solute, the solvent and the dispersant are 10-30wt%, 65-85wt% and 1-5wt% respectively.
[0015] The substrate is a flexible substrate, a paper substrate or a glass substrate.
[0016] The flexible substrate is a polyimide (PI) film or a polyethylene terephthalate (PET) film.
[0017] In the step 2, the pre-sintering temperature is 60-80° C., and the pre-sintering time is 5-15 seconds.
[0018] In step 3, the ultrasonic frequency is 20-60 kHz, and the ultrasonic application time does not exceed 5 seconds.
[0019] The present invention also provides a conductive pattern prepared according to the above-mentioned high-efficiency metal ink ultrasonic assisted sintering method.
[0020] The present invention also provides an application of a conductive pattern prepared by the above-mentioned high-efficiency metal ink ultrasonic assisted sintering method in electronic components, flexible antennas and high-precision printed circuits.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. Improved conductivity: The present invention uses ultrasonic assisted sintering of nanosilver ink to obtain a conductive pattern with a conductivity of 2.6×10 7 S / m, which significantly improves the conductive properties of the conductive pattern compared with the traditional high-temperature sintering method.
[0023] 2. Reduced sintering temperature: Compared with the traditional high-temperature sintering method, the present invention introduces ultrasound to enable the sintering of metal ink at a lower temperature, thereby avoiding damage to the substrate caused by high temperature, expanding the types of substrates that can be used, and reducing the energy consumption of the process.
[0024] 3. Improved sintering quality: The present invention adopts an ultrasonic assisted sintering process to generate frictional heat and plastic deformation between metal particles, thereby forming a more dense conductive pattern, reducing porosity, and improving the quality of the conductive pattern.
[0025] 4. Simple process and energy saving: The whole preparation process of the present invention does not require complicated equipment, has low energy consumption, and is suitable for large-scale industrial application.
[0026] In summary, the present invention significantly reduces the temperature requirement during the sintering process by introducing ultrasound, making the substrate material less susceptible to heat damage, thereby expanding the types of substrates that can be used, such as flexible plastics, paper substrates, etc.; at the same time, through the local friction heat generation and plastic deformation induced by ultrasound, the metal particles can be more tightly combined, significantly reducing the sintering temperature while improving the conductive performance of the conductive pattern; the present invention has the advantages of simple process, little damage to the substrate, and excellent conductive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a flow chart of the high-efficiency metal ink ultrasonic assisted sintering method provided by the present invention.
[0028] Figure 2 The SEM images of the conductive patterns prepared in Example 3 and Comparative Example 1 of the present invention, wherein: Figure 2 (a) is Example 3, Figure 2 (b) is Comparative Example 1.
[0029] Figure 3 The resistance test of the conductive pattern prepared in Example 3 of the present invention and Comparative Example 1, wherein: Figure 3 (a) is Example 3, Figure 3 (b) is Comparative Example 1. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is further described in detail in conjunction with the drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0031] A high-efficiency ultrasonic-assisted sintering method for metal ink comprises the following steps:
[0032] Step 1: Apply metal ink to the surface of the substrate to form a conductive pattern with a preset thickness;
[0033] The metal ink is printed and coated onto the surface of the substrate by an inkjet printer; the metal ink is nano silver ink or nano copper ink, the viscosity of the metal ink is 1-10 mPa·s, and the surface tension is 25-45 mN / m, so as to ensure the accuracy and uniformity of the printed pattern; the metal ink is prepared by a solute, an organic solvent and a dispersant, the solute is nano silver or nano copper particles with a particle size of 20-100 nm, the solvent is an organic solvent with a low boiling point and good volatility, specifically propanol, ethanol or ethylene glycol, so as to ensure the rapid volatilization of the solvent during the subsequent low-temperature heating process, and the dispersant is polyvinyl pyrrolidone (PVP), so as to ensure the stability and uniform coating performance of the ink; the mass percentages of the solute, the solvent and the dispersant are 10-30wt%, 65-85wt% and 1-5wt% respectively; the substrate is a flexible substrate, a paper substrate or a glass substrate, and the flexible substrate is specifically a polyimide (PI) film or a polyethylene terephthalate (PET) film;
[0034] Step 2: After the metal ink is coated, the substrate with the conductive pattern in step 1 is pre-sintered at a low temperature to evaporate part of the solvent in the metal ink; the pre-sintering temperature is 60-80° C., and the pre-sintering time is 5-15 seconds to prevent the agglomeration of metal particles caused by excessive volatilization, thereby ensuring the uniformity of solvent volatilization;
[0035] Step 3: Apply ultrasonic waves to the surface of the conductive pattern pre-sintered in step 2 to continue low-temperature sintering at a constant temperature. The high-frequency vibration of the ultrasonic waves causes the metal particles to rub against each other, generating heat locally and causing the metal particles to undergo plastic deformation, thereby eventually forming a dense conductive pattern. The ultrasonic frequency is 20-60kHz, and the ultrasonic application time is no more than 5 seconds.
[0036] The present invention also provides an application of a high-efficiency metal ink ultrasonic-assisted sintering method to electronic components, flexible antennas and high-precision printed circuits.
[0037] Example 1
[0038] A high-efficiency ultrasonic-assisted sintering method for metal ink comprises the following steps:
[0039] Step 1: using an inkjet printer to apply nanosilver ink to the surface of a polyimide (PI) film to form a conductive pattern with a thickness of 100 μm;
[0040] The nanosilver ink is prepared by 15wt% of nanosilver particles, 80wt% of ethanol and 5wt% of polyvinyl pyrrolidone (PVP) by mass percentage, the viscosity of the nanosilver ink is 3mPa·s, the surface tension is 25mN / m; the average particle size of the nanosilver particles is 100nm;
[0041] Step 2: After the nanosilver ink is coated, the polyimide (PI) film with the conductive pattern in step 1 is pre-sintered at 70° C. for 10 seconds to evaporate part of the solvent in the nanosilver ink;
[0042] Step 3: Apply ultrasonic waves to the surface of the conductive pattern pre-sintered in step 2 to continue low-temperature sintering at a constant temperature. The high-frequency vibration of the ultrasonic waves causes the metal particles to rub against each other, generating heat locally and causing the metal particles to undergo plastic deformation, thereby eventually forming a dense and uniform conductive pattern suitable for flexible circuits. The ultrasonic frequency is 20 kHz and the ultrasonic application time is 3 seconds.
[0043] Example 2
[0044] A high-efficiency ultrasonic-assisted sintering method for metal ink comprises the following steps:
[0045] Step 1: using an inkjet printer to apply nano copper ink to the surface of a polyethylene terephthalate (PET) film to form a conductive pattern with a thickness of 100 μm;
[0046] The nano copper ink is prepared by 20wt% of nano copper particles, 75wt% of propanol and 5wt% of polyvinyl pyrrolidone (PVP) by mass percentage, the viscosity of the nano copper ink is 7mPa·s, the surface tension is 45mN / m; the average particle size of the nano copper particles is 50nm;
[0047] Step 2: After the nano copper ink is coated, the polyethylene terephthalate (PET) film with the conductive pattern in step 1 is pre-sintered at 80° C. for 8 seconds to evaporate part of the solvent in the nano copper ink;
[0048] Step 3: Apply ultrasonic waves to the surface of the conductive pattern pre-sintered in step 2 to continue low-temperature sintering at a constant temperature. The high-frequency vibration of the ultrasonic waves causes the metal particles to rub against each other, generating heat locally and causing the metal particles to undergo plastic deformation. The copper particles form a dense conductive layer suitable for flexible electronics and sensors. The ultrasonic frequency is 40 kHz and the ultrasonic application time is 4 seconds.
[0049] Example 3
[0050] A high-efficiency ultrasonic-assisted sintering method for metal ink comprises the following steps:
[0051] Step 1: using an inkjet printer to apply nanosilver ink to the surface of a poly-glass substrate to form a conductive pattern with a thickness of 100 μm;
[0052] The nanosilver ink is prepared by 25wt% of nanosilver particles, 70wt% of ethylene glycol and 5wt% of polyvinyl pyrrolidone (PVP) by mass percentage, the viscosity of the nanosilver ink is 10mPa·s, the surface tension is 37mN / m; the average particle size of the nanosilver particles is 20nm;
[0053] Step 2: After the nanosilver ink is coated, the glass substrate with the conductive pattern in step 1 is pre-sintered at 60° C. for 15 seconds to evaporate part of the solvent in the nanosilver ink;
[0054] Step 3: Apply ultrasonic waves to the surface of the conductive pattern pre-sintered in step 2 and continue low-temperature sintering at a constant temperature. The high-frequency vibration of the ultrasonic waves causes the metal particles to rub against each other, generating heat locally and causing the metal particles to undergo plastic deformation, thereby eventually forming a dense and uniform conductive pattern suitable for hard substrate electronics, such as touch screen electrodes. The ultrasonic frequency is 60 kHz and the ultrasonic application time is 5 seconds.
[0055] Comparative Example 1
[0056] Nanosilver ink was applied to the surface of a polyimide (PI) film using an inkjet printer to form a conductive pattern with a thickness of 100 μm. The nanosilver ink was prepared by 25 wt% of nanosilver particles, 70 wt% of ethylene glycol and 5 wt% of polyvinyl pyrrolidone (PVP) in terms of mass percentage. The viscosity of the nanosilver ink was 10 mPa·s and the surface tension was 37 mN / m. The average particle size of the nanosilver particles was 20 nm. The polyimide (PI) film with the conductive pattern was then sintered at 180°C for 10 minutes.
[0057] Post-sintering treatment and performance testing
[0058] After sintering, the conductive pattern is surface cleaned with isopropyl alcohol to remove residual solvent or surface oxides and improve conductivity; it is then dried in a vacuum.
[0059] In order to evaluate the effect of the present invention, the microstructure and conductive properties of the sintered conductive pattern were tested.
[0060] Figure 2 The SEM images of the conductive patterns prepared in Example 3 and Comparative Example 1 of the present invention, wherein: Figure 2 (a) is Example 3, Figure 2 (b) is comparative example 1; Figure 2 (a) It can be seen that compared with the traditional high-temperature sintering method (porosity: 14.06%), the conductive pattern prepared by the present invention has fewer pores on the surface, with a porosity of 6.02%, indicating that the conductive pattern prepared by the ultrasonic assisted sintering method of the present invention has lower porosity and higher density.
[0061] Figure 3 The resistance test of the conductive pattern prepared in Example 3 of the present invention and Comparative Example 1, wherein: Figure 3 (a) is Example 3, Figure 3 (b) is comparative example 1; Figure 3 (a) It can be seen that compared with the traditional high temperature sintering method (resistance: 254.5Ω), the resistance of the conductive pattern prepared by the present invention is 0.3Ω, indicating that the resistance performance of the conductive pattern prepared by the ultrasonic assisted sintering method of the present invention is significantly improved.
[0062] The present invention uses RTS-9 dual-electrical four-probe tester to test the conductive patterns prepared in Example 3 and Comparative Example 1. Compared with the traditional high-temperature sintering method (conductivity: 1.2×10 7 S / m), the conductivity of the conductive pattern prepared by the ultrasonic assisted sintering method of the present invention is 2.6×10 7 S / m, indicating that the ultrasonic assisted sintering method of the present invention can significantly improve the conductivity of the conductive pattern.
Claims
1. A highly efficient ultrasonic assisted sintering method for metal ink, characterized in that: The steps include: Step 1: Apply metal ink to the surface of the substrate to form a conductive pattern with a preset thickness; Step 2: After the metal ink is coated, the substrate with the conductive pattern in step 1 is pre-sintered at a low temperature to evaporate part of the solvent in the metal ink; Step 3: Apply ultrasonic waves to the surface of the conductive pattern pre-sintered in step 2 to continue low-temperature sintering at a constant temperature, and finally form a dense conductive pattern.
2. A high-efficiency ultrasonic assisted sintering method for metal ink according to claim 1, characterized in that: In step 1, the metal ink is nano silver ink or nano copper ink, the metal ink has a viscosity of 1-10 mPa·s, and a surface tension of 25-45 mN / m.
3. A high-efficiency metal ink ultrasonic assisted sintering method according to claim 2, characterized in that: The metal ink is prepared from a solute, an organic solvent and a dispersant. The solute is nanosilver or nanocopper particles with a particle size of 20-100 nm, the organic solvent is propanol, ethanol or ethylene glycol, and the dispersant is polyvinyl pyrrolidone (PVP); the mass percentages of the solute, the solvent and the dispersant are 10-30wt%, 65-85wt% and 1-5wt% respectively.
4. The high-efficiency ultrasonic-assisted sintering method of metal ink according to claim 1, characterized in that: The substrate is a flexible substrate, a paper substrate or a glass substrate.
5. A high-efficiency ultrasonic-assisted sintering method for metal ink according to claim 4, characterized in that: The flexible substrate is a polyimide (PI) film or a polyethylene terephthalate (PET) film.
6. The high-efficiency ultrasonic-assisted sintering method of metal ink according to claim 1, characterized in that: In the step 2, the pre-sintering temperature is 60-80° C., and the pre-sintering time is 5-15 seconds.
7. The high-efficiency ultrasonic-assisted sintering method of metal ink according to claim 1, characterized in that: In step 3, the ultrasonic frequency is 20-60 kHz, and the ultrasonic application time does not exceed 5 seconds.
8. A conductive pattern prepared by the high-efficiency metal ink ultrasonic assisted sintering method according to any one of claims 1 to 7.
9. Use of a conductive pattern prepared by the high-efficiency metal ink ultrasonic assisted sintering method as described in any one of claims 1 to 7 or a conductive pattern as described in claim 8 in electronic components, flexible antennas and high-precision printed circuits.